Mapping Global Trends in Renewable Energy Research: A Bibliometric Analysis and Systematic Literature Review - Zharif, Erza Arkan; Siswanto, Andika Prayoga; As-Silmy, Muhammad Ashbar; Septiawan, Bani; Lubis, Putri Bintang; Misnaini; Abdillah, Akbar (Jurnal Bio-Geo Material Dan Energi, 2026)
This study aims to analyze global research trends in renewable energy to support sustainable energy transition using a combined approach of Systematic Literature Review (SLR) based on PRISMA and bibliometric analysis. Data were collected from the Scopus database for the period 2022–2026, with a total of 2500 selected documents using a threshold-based selection method. The analysis was conducted using VOSviewer and Bibliometrix (RStudio) to map keyword networks, author collaborations, and publication distributions. The results indicate a significant increase in renewable energy research, with dominant themes including renewable energy, sustainable development, and alternative energy. The findings also reveal several major research clusters related to clean energy technologies and energy management systems. Research collaboration is dominated by countries such as China, the United States, and India. This study contributes by providing a comprehensive mapping of research trends and identifying future research opportunities to support the global sustainable energy transition